Biomechanics of Third Window Syndrome - Iversen, Marta M.; Rabbitt, Richard D. (Frontiers in Neurology, 2020)
Third window syndrome describes a set of vestibular and auditory symptoms that arise when a pathological third mobile window is present in the bony labyrinth of the inner ear. The pathological mobile window (or windows) augment the oval and round windows, and disrupt normal auditory and vestibular function by altering biomechanics of the inner ear. The most commonly occurring third window syndrome arises from superior semicircular canal dehiscence (SSCD), where a section of bone overlying the superior semicircular canal is absent or thinned. The presentation of SSCD syndrome is well characterized by clinical audiological and vestibular tests. In this review, we describe how the third compliant window introduced by a SSCD alters the biomechanics of the inner ear and thereby leads to vestibular and auditory symptoms. Understanding the biomechanical origins of SSCD further provides insight into other third window syndromes and the potential of restoring function or reducing symptoms through surgical repair.